Avaliação da consistência da indexação em bibliotecas universitárias federais da região nordeste do Brasil - Dal'Evedove Tartarotti, Roberta Cristina [UNESP]; Dal'Evedove, Paula Regina; Fujita, Mariângela Spotti Lopes [UNESP] (My University, 2017)
In automated retrieval systems, the proper use of the indexing language is essential because it allows the representation of document content compatible with the users' search requests in an area of specialization. Through the quantitative methodology of the Evaluation of Indexing, it was possible to carry out a diagnostic study of thematic representation of books in online catalogs of university libraries. The universe of study was 9 federal university libraries in the Northeast Region of Brazil. The results showed an average of 46.99% consistency between the indices for the relaxed index, while the average was 39.21% with the rigid index. As final considerations, there are still several factors that influence the quality of the indexing, being necessary more theoretical-methodological studies in the area. In addition, other complementary studies from other Brazilian regions could provide a current and broader picture of the quality of the indexing process in information retrieval systems of university libraries in the Brazilian context.
Evaluation of indexing consistency at federal university libraries in northwestern of Brazil
Keywords: Brazilian university libraries; Indexing consistency; Indexing evaluation; Online catalogs